Lack of Relationship between Alu Repetitive Elements in Angiotensin Converting Enzyme and the Severity of Diabetic Retinopathy - Abu-Hassan, Diala (Journal of Medical Biochemistry, 2021)
Background: Angiotensin converting enzyme (ACE) stimulates angiogenesis that leads to the development of diabetic retinopathy (DR). Alu repetitive elements in ACE gene increase the expression of this enzyme. We investigated the frequency of Alu repetitive elements, insertion/deletion (I/D) polymorphism, in angiotensin converting enzyme among diabetic retinopathy patients and whether this polymorphism is associated with the severity of retinopathy in Jordanians with type 2 diabetes. Methods: A total of 277 subjects participated in this case/ control study (100 diabetic patients without DR, 82 diabetic patients with DR, and 95 healthy control). Blood samples were withdrawn followed by DNA extraction. Alu repetitive elements were examined by polymerase chain reaction followed by gel electrophoresis. Results: The genotype and allele frequencies among diabetic patients, were close to healthy controls (genotypes, II 44.4 vs. 44.7%, ID 44.4 vs. 42.6%, DD 12.2 vs. 12.8%, P=0.402 and 0.677 respectively, alleles, I 65.6 vs. 66%, D 34.4 vs. 34%, P=0.863, respectively). Complicated diabetics with retinopathy showed similar genotype and allele frequency to those without complications. The severity of diabetic retinopathy in affected individuals was not correlated with I/D polymorphism (P=0.862). Conclusions: We conclude that the presence of Alu repetitive elements did not increase the development or progression risk to retinopathy in Jordanian type 2 diabetic patients. No association between I or D alleles with the severity of DR was detected.